Pengaruh Social Media Influencer terhadap Brand Loyalty Tiktok dengan Purchase Intention sebagai Mediasi pada Generasi Z di Indonesia - Indira Rachmawati (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Generation Z is known to be very familiar with technology and often uses social media, especially TikTok. The beauty and skincare industry in Indonesia uses influencer marketing as the main strategy to promote their products and services. This study used quantitative methods with purposive sampling techniques, involving 385 respondents through online questionnaires. The analysis was performed using Structural Equation Modeling (SEM) with SmartPLS version 4.0.9.9 for Windows. The results showed that social media influencers have a positive and significant influence on purchase intention and brand loyalty, both directly and through purchase intention as mediation. The use of social media influencers can increase brand appeal and strengthen branding at minimal cost, especially for the younger generation. This research provides further insight into how social media influencers can shape positive customer perceptions and build brand loyalty. Further research is recommended to consider additional variables such as brand image and reputation, as well as expand the scope of the social media platforms studied.